Requirements for successful privatization: Lessons from the Treuhandanstalt's approach - Klaus-Dieter Schmidt (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1995)
The paper analyses the Treuhandanstalt's privatization approach by putting it in a public choice perspective. It comes to the conclusion that the Treuhandanstalt had been very successful in reaching its economic and social targets. Economists might worry that the Treuhandanstalt's operation had accumulated too much waste caused by social considerations. And politicians might lament that its strategy implied that millions of people were ,,outplaced or ,,downsized in the name of privatization. But in terms of the interaction of economics and politics the Treuhandanstalt's performance had not been so far from the optimum.
Keywords: 330